Analysis of information-telecommunication network risk based on cognitive maps and cause-effect diagram - Kosenko, Viktor; Malyeyeva, Olga; Persiyanova, Elena; Rogovyi, Anton (НТУ "ХПІ", 2017)
The subject matter of the article is the processes of analysis and risk assessment of information and telecommunications networks. The aim is to reduce the potential losses caused by the risks of information and telecommunications network (ITN) functioning by taking timely risk management measures. The objectives are: classification of ITN risks, highlighting the main factors and causes of their occurrence; formation of a systematic presentation of risks to identify their manifestation and consequences; development of the method for assessing the influence of the risk and private risk on probable consequences; obtaining a quantitative risk assessment of ITN. The methods used are: system analysis of risks, method of cognitive maps, cause-and-effect analysis. The following results are obtained: classification of private risks of ITN according to the reasons and the factors of their occurrence is made; the negative consequences affecting the basic characteristics of the operation of ITN are defined; as a result, the structural system model of ITN risks is formed, in which the relationships between the elements of the main aspects of risk are shown; the method based on the theory of causal analysis is suggested in order to quantify the risk impact on ITN functioning. The risk model is based on the construction and analysis of probabilistic or fuzzy cognitive maps. Experts estimate the level of influence of private risks on the characteristics of the network in order to make decisions on risk management. The generalized structure of the cause-effect diagram of the risk factors, manifestation and consequences is developed; on ITN basis the method for quantifying the probability of risk consequences is suggested. The quantitative assessment of probable malfunctioning of the network that is determined by a specific effect (taking into account ITN probability), which is caused by private risks is also made. Conclusion. The suggested approach for quantitative assessment of ITN risk is based on the method of cause-and-effect analysis and enables taking into account both the factors causing it and probable consequences. The obtained results can be used to determine probable failures and losses in ITN functioning on the basis of the information about the degree of risk factors effects, risk events and consequences, and the cause-effect relationships between them. Thus, potential losses can be identified; measures to manage the risks of ITN functioning can be taken.

Предметом вивчення в статті є процеси аналізу та оцінки ризиків інформаційно-телекомунікаційних мереж. Мета - зниження потенційних втрат, зумовлених ризиками функціонування інформаційно-телекомунікаційної мережі (ІТМ), шляхом своєчасного вжиття заходів з управління ризиками. Завдання: класифікація ризиків ІТМ з виділенням основних факторів і причин їх виникнення; формування системного уявлення ризиків для виявлення їх проявів і наслідків; розробка методу оцінки ступеня впливу причин на прояв ризику і приватних ризиків на можливі наслідки; отримання кількісної оцінки ризиків ІТМ. Використовуваними методами є: системний аналіз ризиків, метод когнітивних карт, причинно-наслідковий аналіз. Отримані такі результати. Проведена класифікація приватних ризиків ІТМ з причин та за факторами їх виникнення. Визначено негативні наслідки, що негативно впливають на основні характеристики функціонування ІТМ. В результаті сформована структурна системна модель ризиків ІТМ, в якій відображені взаємозв'язки між елементами основних аспектів ризику. Для кількісної оцінки впливу ризику на функціонування ІТМ запропонований метод, заснований на теорії причинного аналізу. Модель ризиків заснована на побудові та аналізі імовірнісних або нечітких когнітивних карт. Для прийняття рішень з управління ризиками експертами визначається рівень впливу приватних ризиків на характеристики мережі. Розроблено узагальнену структуру причинно-наслідкової діаграми чинників, проявів і наслідків ризиків. На її основі запропоновано спосіб кількісної оцінки можливості виникнення наслідків ризиків. Також проводиться кількісна оцінка можливих збитків для функціонування мережі, що визначається конкретним наслідком (з урахуванням його ймовірності), який викликаний приватними ризиками. Висновки. Запропоновано підхід для кількісної оцінки ризику ІТМ заснований на методі причинно-наслідкового аналізу та дозволяє враховувати як чинники, що його викликають, так й можливі наслідки. Отримані результати можна використовувати для визначення можливих збоїв і втрат при функціонуванні ІТМ на основі інформації про ступінь впливу факторів ризику, ризикових подій і наслідків, а також причинно-наслідкових залежностей між ними. Стає можливим визначати потенційні втрати, а також вживати заходів з управління ризиками функціонування ІТМ.
Аналіз ризиків інформаційно-телекомунікаційної мережі на основі когнітивних карт і причинно-наслідкової діаграми
Keywords: information-telecommunication network; risk factors; consequences; cause-effect diagram; influence factors; інформаційно-телекомунікаційна мережа; фактори; ризики; наслідки; причинно-наслідкова діаграма; коефіцієнти впливу